Life Goes on: Hard Bread and Lyricism on the Island of the Sponge Divers (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
On the Aegean island of Kalymnos they make hard bread. The koulouria baked each morning on Symi are rings of white dough coated with sesame seeds, crisp on the outside, soft in the middle, and stale by midday. But the distinctive bread of Kalymnos, krithini kouloura or paximadia, is a rusk made of tough barley flour fermented with anise and mastic, and slow- baked to an unrelenting hardness to last six months at sea. The people too have a reputation for being tough, divers especially. Much of the mountainous island is rock, and in the Kalymnian stories of sponge diving, there’s a special pride in qualities of extreme endurance. Since the divers had always been champions whose manhood was intimately linked to acts of daring, once the deep-sea diving suit they called the skafandro, the man-boat, became available in the mid-1860s, the modern dangers of the new diving tech were easily assimilated into an old code of heroism. Or at least this was how it seemed to the cultural anthropologist H. Russell Bernard when he studied the Kalymnian sponge fishing industry in the 1960s.